Learning strategies and academic performance in the executive secretarial course students, Machala – Ecuador - Betancourt-Pereira, Jessenia (2020)
The main objective of the research was to know the relationship between the learning strategies and the academic performance in the executive secretarial course students. This was a descriptive level research with correlational design. The population and sample was constituted of 25 students. Two instruments were applied: the survey technique and the structured questionnaire instrument to measure the learning strategies variable, another measuring instrument was a checklist with the final report card of the students of fourth semester to measure the academic performance variable, these instruments were evaluated and validated through expert judgment reaching a level of reliability of 0.921, which has a high level of reliability. To measure the correlation that exists between both variables, the Pearson's correlation coefficient was used, where it was observed that there is a correlation of 0.846, where it is shown that there is a significant relationship; In other words, as the learning strategies are applied, a good academic performance is produced in the sample studied. It was concluded that there is a significant relationship between the learning strategies and the academic performance of the students with a 95% confidence level.